HUBUNGAN MOTIVASI BELAJAR DENGAN PENYESUAIAN DIRI MAHASISWA PROGRAM STUDI BIMBINGAN DAN KONSELING PENDIDIKAN ISLAM SEMESTER 2 UNIVERSITAS ISLAM NEGERI SALATIGA - Enggal Andini Rismanike; Kaila Tata Nur Islamay; Farcha Rachelia Masruroh (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Learning motivation is a factor that plays a role in helping students cope with academic demands and adapt to the university environment. Early-semester students often face various challenges—both academic and social—making the ability to adjust a crucial aspect of academic success. This study aims to determine the relationship between learning motivation and the adjustment of second-semester students in the Islamic Education Guidance and Counseling Study Program at the State Islamic University (UIN) Salatiga. The study employs a quantitative approach with a correlational design. The population consisted of 116 students, with a sample of 52 students selected using simple random sampling. Data collection was conducted using a questionnaire that had undergone validity and reliability testing. Data analysis involved descriptive statistics and the Pearson Product Moment correlation test, utilizing IBM SPSS Statistics software. The results indicate that the students' learning motivation falls within the moderate-to-high range, as does their level of adjustment. The correlation test results reveal a positive and significant relationship between learning motivation and adjustment (r = 0.288; p = 0.038 < 0.05), although the strength of the relationship is categorized as weak. These findings suggest that higher learning motivation is associated with better adjustment capabilities when facing academic demands and the university environment.